TINGKAT KECEMASAN IBU DENGAN ANAK TUNA GRAHITA BERDASARKAN HAMILTON ANXIETY RATING SCALE (HAM-A) DI SEKOLAH LUAR BIASA C DAN C1 NEGERI KOTA DENPASAR TAHUN 2014 - Ariesti, Brilliana Firly; Ardani, Indah (E-Jurnal Medika Udayana; Vol 6 No 3 (2017): E-jurnal medika udayana, 2017)
Anxiety disorders are among the most common mental disorders were found. Where substantial factors including gender, age, culture, conflict and economic status, and place of residence have a big impact. Parents, especially mothers with intellectual disability children have more problems and tend to have higher levels of anxiety than women with normal children. This study aims to determine the level of maternal anxiety with intellectual disability children and with the distribution by age group, marital status, educational status, and occupational status. This study has been done at Denpasar special schools C and C1 since August through October 2014. The research method is using observational descriptive method of research with cross sectional design. The result is analyzed by univariate and bivariate without statistic test using SPSS 17. According to 76 research subject, 55.3% with age between 41-50 years old, 46.1% high school graduated, 97.4% married, and almost equivalent of occupational status. Most of 77% mothers do not have anxiety, 16% mild anxiety, 3% moderate anxiety, and 4% severe anxiety. Highest anxiety symptom is shown as somatic muscle symptom as much as 50%. Higher level of anxiety is suffered by mothers with low level of intellectual disability children. Can be concluded that a lot of mothers are not anxious with her children condition. As for the distribution of anxiety level, the highest is on mothers with low level of intellectual disability children, mother with age between 41-50 years old, high school graduated, married, and not working.
Keywords: Mother’s anxiety level, intellectual disability, HAM-A